Children's war experiences, coping strategies and stress reactions - Franc, Renata (Array, 1998)
The aim of the study was to investigate the specific kinds of war stressors to which Croatian children were exposed to and to examine the predictivity of those war stressors, children`s coping strategies and their gender on the level of intrusive stress reactions reported by the children of different age. The sample consisted of N=563 elementary school children from regions of Croatia differently affected by war. Main finding of the study is that, in comparasion to children`s coping strategies and gender, exposure to war stressors is the most important predictor of children`s psychological symptoms of intrusion as the main symptom of posttraumatic stress reaction.